Metabolismo energético e emissão de compostos orgânicos por Hevea spruceana (Benth.) Müll. Arg em diferentes ecossistemas inundáveis da Amazônia Central - Liberato, Maria Astrid Rocha (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
About 6% of the amazon region corresponds to areas flooded by lateral overflow of the waters of rivers and lakes after the period of highest rainfall in catchment areas, thanks to the annual flood pulse. According to the geology of the drainage basin, the physico- chemical of river water may vary, being detectable in the Amazon two large groups of wetlands: the várzea, flooded by white water rivers, and the igapó, inundated by rivers of clear or black waters. The biota established in these two wetland types developed morphological and anatomical peculiarities, as well as physiological adaptations that are reflected in their primary (e.g. photosynthetic capacity) and secondary (e.g. emission of volatile organic compounds) metabolism. No wonder then that the composition of tree species is largely different between the várzea and the igapó. However, some species occur in both wetland types, and the nature of this distribution is poorly explored by science so far. Hence, the present study was designed with the premise that knowledge of the physiological processes can help to elucidate the mechanisms of adaptability of tree species of Amazonian flooded environments against different environmental conditions as well as the implications of these mechanisms for plants and environments. To this end, it was chosen the tree species Hevea spruceana (Benth.) Müll. Arg., of natural occurrence at várzea and igapó environments in Central Amazonia, to comparatively study the phenology, the seeds organic reserves, and the temporal and morphophysiological aspects of germination. Additionally, it was monitored the ecophysiological behavior in seedlings and were analyzed the nutrient content, chlorophyll concentration, gas exchange, and the emission of volatile organic compounds, under flooded and not flooded conditions. The results showed no differences between the responses of Hevea spruceana populations of várzea and igapó, concerning phenology, fruit, seeds and its reserves and the germination process. However, the ecophysiological evaluation revealed significant differences. The assimilation of CO 2 was higher for plants of the igapó. The main responsible for this difference seems to be the photorespiration, higher in plants of the várzea along the entire hydrologic cycle. On the other hand, the greater uptake of carbon from igapó plants through photosynthesis, rather than be led to a greater growth of plants of such environments, seems to be drained through a production of VOCs, more than twice as high in igapó plants, while under flooding. This performance contrasts in photosynthesis and production of volatile organic compounds from young plants of H. spruceana colonizing these two types of flooded amazon suggests that the species has genetic variability that allows the expression of distinct adaptive physiological processes in each of these environments. The phenotypic plasticity is manifested by the existence of different ecophysiological ecotypes, in order to allow the specie to successfully colonize environments with contrasting physico-chemistry. Whether or not this pattern can be observed for other species colonizing the igapó deserves further studies because it can show an important ecophysiological pattern for the plant community of these environments that may have then a greater importance than that previously postulated in terms of balance of gases in regional level and global climate change.
Keywords: Ecofisiologia vegetal; Seringueira; Hevea spruceana